Occlusal stamp, renovation to restorative technique: a case series - Shrestha, Kriti; Arora, Chetna; Gautam, Vanita; Shubham, Snigdha; Tripathi, Rupam; Nepal, Manisha; Karki, Ateet (Journal of Chitwan Medical College, 2021)
Maintaining the contact and contour point is very difficult task in composite restoration which requires expertise hand and is time consuming. The occlusal stamp technique has been developed to facilitate the work of dental professional and achieve aesthetic and functional results. A precise tooth like restoration with an accurate functional occlusion is obtained when the stamp technique is performed. Therefore, the aim of this case report was to present clinical cases in which the stamp technique was performed to replicate the original and well controlled occlusal anatomy, so less time is required for finishing and polishing.